Resultados exergéticos, exergoeconômicos e exergoambientais de uma planta de cogeração com microturbina a gás integrada a uma unidade de destilação com múltiplos efeitos - Santos, Erick Breno Azevedo dos (2023)
The distribution of drinking water is one of the most problems social of humanity, mainly due to scarcity of fresh water in some regions of the world. Hence, desalination has gained more significance, because it is an attractive solution owing to the large volume of seawater. In recent years, technological advances in cogeneration have provided significant improvements in thermal desalination. Nevertheless, the production of desalinated water still has a high operating cost for most countries. Thus, increasing the efficiency of the system components and reducing the costs associated with each one of them become fundamental parts for the improvement of the process. Therefore, this work presents the modeling and evaluation of a 30kW gas microturbine power plant integrated into a multi-effect distillation unit with thermal vapor compression (MED-TVC). The energetic, exergetic, exergoeconomic and exergoenvironmental analyses of the plant were developed by the SPECO method. The plant has presented a production of 29.69 m3/day of desalinated water for 0.04033 kg/s of motive steam, resulting in Gain Output Ratio (GOR) of 8.52. In addition, the exergetic efficiency increased from 13.84% to 23.39% with the use of cogeneration. The exergy destroyed in the desalination unit represented only 18% of the total. The average cost per exergy unit of electricity was 94.73 US$/GJ and the cost of desalinated water produced was 5.6 US$/m3. The exergoeconomic analysis indicated that investments in improvements in generator, effect 1 and regenerator efficiency are fundamental for the economic optimization of the plant. The specific environmental impact of electricity was 13892 mPt/GJ, while that of desalinated water was 14645 mPt/GJ. The environmental results showed that improvements in the regenerator, effect 1, HRSG and generator are crucial for the plant's best environmental performance.